The pathogenetic role of some cytokines in the development and course of various clinical forms of urinary tract infections in children - Lezhenko, H. O.; Zakharchenko, N. A.; Леженко, Геннадій Олександрович; Захарченко, Наталія Анатоліївна (My University, 2022)
The purpose of the research: to study the content of interleukin-6 and interleukin-15 cytokines in the blood serum of children with urinary tract infection and to establish their pathogenetic role in the development of various clinical forms of the disease. Materials and methods. The study groups consisted of 84 children (mean age of 10.0 ± 1.3 years). The main group was divided into subgroups: the first one — 17 children with acute pyelonephritis, the second — 21 patients with chronic pyelonephritis, the third — 16 children with acute cystitis, the fourth subgroup — 10 patients with unspecified urinary tract infections. The control group included 20 relatively healthy children. The content of interleukin-6 and interleukin-15 was evaluated by enzyme-linked immunosorbent assay. Results. It was established that the development of acute urinary tract infections was accompanied by a high level of serum pro-inflammatory interleukin-6. We found the highest level in children with cystitis, which exceeded that of the control group by 2.8 times (р < 0.01). In children with acute pyelonephritis, this cytokine was 1.8 times higher (р < 0.05). However, patients with chronic pyelonephritis had only a tendency towards its increase (p > 0.05). Interleukin-15 in the main group was statistically higher than in controls (р < 0.05). In children of subgroups 3 and 4, its level did not differ from that of the control group (p > 0.05). However, in subgroups 1 (р < 0.05) and 2 (р < 0.01), we observed a statistically significant increase in interleukin-15 level. A direct correlation between interleukin-15 content and disease duration (r = 0.64, р < 0.05) was also found. Conclusions. The development of an acute inflammatory process in the urinary tract in children occurs against the background of a marked increase in the expression of interleukin-6, while a chronic inflammatory process develops with a statistically significant increase in the level of interleukin-15 in blood serum. Мета роботи. Дослідити вміст цитокінів інтерлейкіну-6 та інтерлейкіну-15 у сироватці крові дітей з інфекцією сечовидільної системи та встановити їх патогенетичну роль у розвитку різних клінічних форм хвороби. Матеріали та методи. Групи дослідження становили 84 дитини (середній вік — 10,0 ± 1,3 року). Основну групу розділили на підгрупи: 1-ша — 17 дітей, хворих на гострий пієлонефрит; 2-га — 21 пацієнт із хронічним пієлонефритом; 3-тя — 16 дітей, хворих на гострий цистит; 4-та — 10 пацієнтів із неуточненими інфекціями сечовидільної системи. Контрольну групу становили 20 умовно здорових дітей. Методом імуноферментного аналізу досліджено вміст інтерлейкіну-6 та інтерлейкіну-15. Результати. Установлено, що розвиток гострих інфекцій сечовивідних шляхів супроводжувався підвищенням рівня сироваткового прозапального інтерлейкіну-6. Найвищим він був у дітей, хворих на цистит, — у 2,8 разa більше за показники контрольної групи (р < 0,01). У пацієнтів із гострим пієлонефритом уміст цитокіну було перевищено в 1,8 разa (р < 0,05). Однак у хворих на хронічний пієлонефрит ми спостерігали лише тенденцію до його зростання (р > 0,05). Рівень інтерлейкіну-15 в основній групі був статистично вищим за показники контрольної групи (р < 0,05). У дітей 3-ї та 4-ї підгруп його вміст не відрізнявся від такого в групі контролю (р > 0,05). Проте в 1-й (р < 0,05) та 2-й (р < 0,01) підгрупах ми спостерігали статистично значуще підвищення рівня інтерлейкіну-15. Також встановлено наявність прямої кореляційної залежності вмісту інтерлейкіну-15 від тривалості захворювання (r = 0,64, р < 0,05). Висновки. Розвиток гострого запального процесу в сечовивідних шляхах у дітей відбувається на тлі вираженого зростання експресії інтерлейкіну-6, тоді як хронічний запальний процес перебігає із статистично значущим підвищенням рівня інтерлейкіну-15 у сироватці крові.
Патогенетична роль деяких цитокінів у розвитку та перебігу різних клінічних форм інфекцій сечовидільної системи в дітей
Lezhenko H. - https://orcid.org/0000- 0003-0851-4586; Zakharchenko N. A. - https://orcid.org/0000- 0002-3956-8571.
Keywords: children; infection of the urinary system; cytokines; діти; інфекція сечовидільної системи; цитокіни